ANALISIS TERHADAP PERAN MAJELIS GEREJA MEMBINA PEMUDA DALAM MORALITAS SEKS di GEREJA PANTEKOSTA DI INDONESIA JEMAAT ARARAT KAMPUNG ADIL - Deni Baso’; Mariati Priskilia (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Theological Analysis of the Role of the Church Council in Fostering Youth in sexual morality in the Pentecostal Church in Indonesia, the Ararat Village Adil Congregation. The purpose of this study is to describe the role of the Church Council in Fostering Youth in Sexual Morality in the Pentecostal Church in Indonesia, the Ararat Village Adil Congregation. The Church Council as a leader, who teaches and pastors in the congregation is a person who is able to influence people or groups of people to achieve common goals and also as a person who is able to solve all problems, thus also able to provide guidance to youth in sexual morality. The results of the study prove that the role of the church assembly in fostering youth in sexual morality is less than optimal. Seeing this, it is hoped that the church council will try to provide guidance to youth in sexual morality because this is very important and needed.